Real Time Monitoring Of Hotspots In Pv Panels Using Iot Technologies - B. Rajesh Kumar, Gayathri Suresh, V. Manimegalai, R. Shobika (International Journal of Modern Agriculture, 2021)
In a world where energy demand is growing, it is important to find creative ways to minimise and save energy. There is a lot of interest in designing an environmentally sustainable device thatsavesmoneyonenergyand maximizes thesolarpanelcostreturnoninvestment.Anew data logger has been developed, installed, programmed, and tested using software & hardware and it has been mounted to be an experimental model in a variety of locations. In areas without connections to the electrical grid or conventional wired telecommunication networks, remote monitoringimprovesthedatalogger'seffectiveness.TheuseoftheInternetofThingsinsolar panel measurement systems which is used to allow the remote control of Photovoltaic (PV) systems, which increases system performance. We present a multifunctional, low-cost, and scalablesystemforPVpanelenvironmentalmonitoringandmeasurementofenergyfromthepanel andenergyconsumptioninthisproject.Thissystemusesanarduino-basedembeddedsystemwith IoTcommunicationforremotedevicemonitoring.Incaseanyproblemoccurredinanyoneofthe panels, it will be replaced by buffer technique. A web/PC based program can be used to track the proposed framework. When the quality parameters of solar power system generation deviate from a predetermined set of standard values, the device sends a warning to a remoteuser.